A Ricardian Analysis of the Impact of Climate Change on African Cropland - Kurukulasuriya, Pradeep (World Bank, Washington, DC, 2012)
This study examines the impact of climate change on cropland in Africa. It is based on a survey of more than 9,000 farmers in 11 countries: Burkina Faso, Cameroon, Egypt, Ethiopia, Ghana, Kenya, Niger, Senegal, South Africa, Zambia, and Zimbabwe. The study uses a Ricardian cross-sectional approach in which net revenue is regressed on climate, water flow, soil, and economic variables. The results show that net revenues fall as precipitation falls or as temperatures warm across all the surveyed farms. In addition to examining all farms together, the study examined dryland and irrigated farms separately. Dryland farms are especially climate sensitive. Irrigated farms have a positive immediate response to warming because they are located in relatively cool parts of Africa. The study also examined some simple climate scenarios to see how Africa would respond to climate change. These uniform scenarios assume that only one aspect of climate changes and the change is uniform across all of Africa. In addition, the study examined three climate change scenarios from Atmospheric Oceanic General Circulation Models. These scenarios predicted changes in climate in each country over time. Not all countries are equally vulnerable to climate change. First, the climate scenarios predict different temperature and precipitation changes in each country. Second, it is also important whether a country is already hot and dry. Third, the extent to which farms are irrigated is also important.